The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00264-013-2094-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose dexamethasone with levobupivacaine improves analgesia after supraclavicular brachial plexus blockade

Abstract: Purpose We conducted ultrasound-guided single-shot supraclavicular blockade and investigated the analgesic effect of dexamethasone added to levobupivacaine. The aim of this study was to determine whether the addition of low-dose dexamethasone to levobupivacaine would prolong the duration of analgesia sufficiently to avoid additional intravenous analgesic use for the first 24 hours postoperatively. Methods This randomised controlled study assessed 70 patients undergoing upper-extremity surgery. Patients were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 14 publications
2
29
0
2
Order By: Relevance
“…2 Another study reported that using ultrasound-guided single-shot supraclavicular blockade with low-dose dexamethasone in a mixture with levobupivacaine results in prolonged analgesia duration and less analgesic use compared with levobupivacaine alone in patient of upper extremity surgery. 18 Trabelsi et al conducted ultrasound-guided supraclavicular brachial plexus block in 60 patients undergoing upper extremity surgery using 15ml of 2% lidocaine plus 2ml of adjuvant (8mg dexamethasone, 100mg tramadol, 2ml saline). They too found a significant prolongation of duration of analgesia with dexamethasone group (1110 min) compared to tramadol group (240 min).…”
Section: Discussionmentioning
confidence: 99%
“…2 Another study reported that using ultrasound-guided single-shot supraclavicular blockade with low-dose dexamethasone in a mixture with levobupivacaine results in prolonged analgesia duration and less analgesic use compared with levobupivacaine alone in patient of upper extremity surgery. 18 Trabelsi et al conducted ultrasound-guided supraclavicular brachial plexus block in 60 patients undergoing upper extremity surgery using 15ml of 2% lidocaine plus 2ml of adjuvant (8mg dexamethasone, 100mg tramadol, 2ml saline). They too found a significant prolongation of duration of analgesia with dexamethasone group (1110 min) compared to tramadol group (240 min).…”
Section: Discussionmentioning
confidence: 99%
“…Hay autores que coinciden con nosotros (26,27,129), al observar un menor requerimiento de mórficos a las 24 horas de la cirugía, pero en la mayoría el consumo se limita sólo a las primeras 24 horas, igualándose posteriormente entre los distintos grupos. Creemos que esta diferencia a las 48 horas con nuestro estudio, pudiera ser debida principalmente, al diseño del estudio por un lado, ya que muchos limitan la observación a las primeras 24 horas, al tipo de cirugía que se realiza en estos estudios, que como ya se ha comentado, el dolor intenso generalmente se limita sólo a las primeras 24 horas, y por supuesto al mejor resultado obtenido en nuestro trabajo en cuanto al tiempo de analgesia del bloqueo femoral con dexametasona se refiere.…”
Section: Consumo De Mórfico Postoperatorio En Función De La Analgesiaunclassified
“…Méthode Des patients subissant une chirurgie des membres supérieurs sous un bloc axillaire du plexus brachial réalisé par échoguidage ont été randomisés à recevoir une dose de dexaméthasone (8 mg) sans agent de conservation par administration intraveineuse (n = 75) ou périneurale (n = 75). L'anesthésique local était identique pour tous les patients de l'étude, lidocaïne 1% et bupivacaïne -0,25% (30 mL) avec 5 lgÁmL Dexamethasone is a common adjuvant for interscalene, [1][2][3][4][5] supraclavicular, [6][7][8][9][10][11][12][13][14][15][16] and axillary [17][18][19] brachial plexus blocks. However, the optimal method of administration remains unknown.…”
Section: Résuméunclassified